Evaluation of Caspase-9b and PP2Acα2 as potential biomarkers for chronic lymphocytic leukemia. Issue 1 (December 2016) - Domínguez-Berrocal, Leticia; Zhang, Xiguang; Zini, Jean; Fominaya, Jesús; Rebollo, Angelita; Bravo, Jerónimo
Abstract Background Disruption of alternative splicing in apoptotic factors has been associated to chronic lymphocytic leukemia among other cancers and hematological malignancies. The proapoptotic proteins Caspase-9 and PP2Acα are functionally related in a direct interaction, which constitutes a promising target for cancer therapy. Both proteins present aberrant mRNA splicing variants that are antiapoptotic (Caspase-9b) and catalytically inactive (PP2Acα2), respectively. Results In this work we have analyzed the relative abundance of the aberrant spliced forms Caspase-9b and PP2Acα2 in several cell lines and chronic lymphocytic leukemia patients and correlated it with several parameters of the disease. Despite 40 % of the patients presented Caspase-9b dysregulation, there was no direct association between alterations in Caspase-9b relative abundance and the parameters analyzed in medical records. More importantly, PP2Acα2 dysregulation was observed in 88 % of CLL patients and was related with advanced stages of the malignancy. Conclusions Caspase-9b dysregulation seemed to be associated with the disease, although the differences between healthy donors and CLL patients were not statistically significant. However, PP2Acα2 dysregulation was significantly different between healthy donors and CLL patients and correlated with Binet B and C stages; therefore, we propose the use of PP2Acα2 dysregulation as a potential biomarker for advanced stages of chronic lymphocytic leukemia.